2021
DOI: 10.4103/japtr.japtr_90_21
|View full text |Cite
|
Sign up to set email alerts
|

Action mode of ursolic acid as a natural antioxidant and inhibitor of superoxide dismutase

Abstract: Recently, the antioxidant is applied for the teeth bleaching treatment as an alternative of toxic material of hydrogen peroxide that is used in teeth bleaching. One of natural sources antioxidant is Uncaria gambir those containing active antioxidant agents. To be applied as a new bioactive constituent in teeth bleaching treatment, a preexperimental study is performed. The aim of the study is to identify the antioxidant constituent of U. gambir and predict their act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Ursolic acid (UA) (3-beta-3-hydroxy-urs-12-ene-28-oic-acid) is a phytochemical with high anticancer potential and is commonly present in many fruits and herbs, such as apples, cranberries, thyme, and lavender . It has gained considerable attention owing to its therapeutic activities and fewer side effects in cancer therapy. , In recent years, the pharmacological effects of UA have been widely investigated, which indicated that UA possesses a wide range of biological activities, including antimicrobial, anti-inflammatory, , antioxidant, , and anticancer. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ursolic acid (UA) (3-beta-3-hydroxy-urs-12-ene-28-oic-acid) is a phytochemical with high anticancer potential and is commonly present in many fruits and herbs, such as apples, cranberries, thyme, and lavender . It has gained considerable attention owing to its therapeutic activities and fewer side effects in cancer therapy. , In recent years, the pharmacological effects of UA have been widely investigated, which indicated that UA possesses a wide range of biological activities, including antimicrobial, anti-inflammatory, , antioxidant, , and anticancer. …”
Section: Introductionmentioning
confidence: 99%
“…2 It has gained considerable attention owing to its therapeutic activities and fewer side effects in cancer therapy. 3,4 In recent years, the pharmacological effects of UA have been widely investigated, which indicated that UA possesses a wide range of biological activities, including antimicrobial, 5−7 anti-inflammatory, 8,9 antioxidant, 10,11 and anticancer. 12−14 Several studies have been investigated the anticancer properties of UA in various types of cancer, including gastric, 15,16 liver, 17 colorectal cancer, 18,19 and breast cancer.…”
Section: ■ Introductionmentioning
confidence: 99%